Exposure to trichloroethylene II. Metabolites in blood and urine. - Vesterberg, Olof; Gorczak, Jadviga; Krasts, Mudite (Scandinavian Journal of Work, Environment & Health, 1976)
Fifteen men were exposed to trichloroethylene (TRI) in three different ways with regard to the concentration of TRI in the air as well as exercise on a bicycle ergometer. The total amount of TRI supplied and taken up by each person was measured. The concentrations of trichloroethanol (TCE) and trichloroacetic acid (TCA) were determined in blood and urine. In spite of large differences in uptake, there were only small differences in the concentration of TCA in blood during the day of exposure. There was a large scatter for the values of TCA in urine within each group. The concentration of TCE in arterial blood increased during exposure. Thereafter the concentrations were almost constant for 2 h and differed among the groups. These results can be interpreted as being due to balanced rates of the formation and elimination of TCE. The levels mentioned were related to the uptake of TRI. The same was found for the rate of excretion of TCE in urine when calculations were made from the morning sample obtained the day after exposure.
Keywords: blood; exposure; metabolite; trichloroacetic acid; trichloroethanol; trichloroethylene; urine